Maternal vitamin D deficiency and developmental origins of health and disease (DOHaD) - Ideraabdullah, Folami Y. (J Endocrinol, 2019)
Vitamin D is an essential nutrient that is metabolized in the body to generate an active metabolite (1,25(OH)(2)D) with hormone-like activity and highly diverse roles in cellular function. Vitamin D deficiency (VDD) is a prevalent but easily preventable nutritional disturbance. Emerging evidence demonstrates the importance of sufficient vitamin D concentrations during fetal life with deficiencies leading to long-term effects into adulthood. Here, we provide a detailed review and perspective of evidence for the role of maternal VDD in offspring long term health, particularly as it relates to Developmental Origins of Health and Disease (DOHaD). We focus on roles in neurobehavioral and cardiometabolic disorders in humans and highlight recent findings from zebrafish and rodent models that probe potential mechanisms linking early life VDD to later life health outcomes. Moreover, we explore evidence implicating epigenetic mechanisms as a mediator of this link. Gaps in our current understanding of how maternal VDD might result in deleterious offspring outcomes later in life are also addressed.